International data acceptance through OECD: history and OECD context - Sigman, Richard (Henry Stewart Talks, 2012)
OECD Council Acts on Mutual Acceptance of Data (MAD), Recognizing assurance from other countries, Collecting information on monitoring programmes via questionnaires, Annual overviews of facilities inspected, Notification to members of non-compliance